An Analysis of Figurative Language Used In The Lyric of I Wanna Be Yours By Arctic Monkeys - Dini Hasanul Awaliyah; Rinaepi (Universitas Islam Al-Ihya Kuningan, 2023)
This research was carried out to help comprehend figurative language and its various forms. Another goal is to determine what kind of figurative language is contained in Arctic Monkeys' song I Wanna Be Yours, as well as the contextual meaning. This research is a descriptive qualitative approach. That is, this study does not calculate data and instead provides an overview of Arctic Monkeys' figurative language in I Wanna Be Yours. This is accomplished by bolding and underlining the song's lyrics, classifying figurative language, and then providing the meaning. The results of this research include the identification of figurative language such as metaphors and similes, as well as the contextual meaning of the lyrics.